The Leased Among Us: Precarious Work, Local Regulation, and the Taxi Industry. (September 2019) - Esbenshade, Jill; Shifrin, Elizabeta
Through a case study of the taxi industry in San Diego, where 89 percent of drivers leased their vehicles as independent contractors (IC), we show how local regulation has enforced precarity. We find that the interaction of policies from various local governmental agencies has actually required lease drivers to operate as ICs and has simultaneously undermined the very control and economic independence that is fundamental to the IC designation. While the literature on precarious employment and IC misclassification tends to emphasize the role of macroeconomic structures, employer action, and federal government policy, this article highlights the role of local regulatory agencies.